2003
DOI: 10.1080/10611860310001647140
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Hydrolytic Enzymes in Tumour Cells is a Determinant for Anti-tumour Efficacy of the Melphalan Containing ProdrugJ1

Abstract: Recently, we presented a series of melphalan containing di- and tripeptides with high cytotoxic activity and J1 (l-melphalanyl-p-l-fluorophenylalanine ethyl ester) was identified as one of the most interesting compounds. It was speculated that the increased activity compared to melphalan itself, demonstrated both in vitro and in vivo, resided in increased transport over the tumour cell membrane and/or hydrolytic cleavage and liberation of melphalan inside the cells. Indeed, overexpression of hydrolytic enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Previous studies showed that lipophilicity and an early intracellular hydrolysis of mel-flufen by peptidases inside the cells to release melphalan contributes to achieving rapid and high intracellular concentrations of melphalan (19,27,28). Earlier findings also showed that in tumor cells a limited exposure time, which simulate short half-life in vivo, proved more favorable for mel-flufen than for melphalan indicating a trapping mechanism through the enzymatic activation (29). Together, these results suggest that mel-flufen administration in patients with multiple myeloma is a more efficient therapeutic strategy for delivering higher concentrations of intracellular melphalan than by directly exposing cells to free melphalan.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies showed that lipophilicity and an early intracellular hydrolysis of mel-flufen by peptidases inside the cells to release melphalan contributes to achieving rapid and high intracellular concentrations of melphalan (19,27,28). Earlier findings also showed that in tumor cells a limited exposure time, which simulate short half-life in vivo, proved more favorable for mel-flufen than for melphalan indicating a trapping mechanism through the enzymatic activation (29). Together, these results suggest that mel-flufen administration in patients with multiple myeloma is a more efficient therapeutic strategy for delivering higher concentrations of intracellular melphalan than by directly exposing cells to free melphalan.…”
Section: Resultsmentioning
confidence: 98%
“…The prodrug J1 has advantage over melphalan in that it provides more efficient intracellular delivery of melphalan, depending on the activity of hydrolytic enzymes [10]. Thus it is anticipated that the activity profile of J1 and melphalan in various tumor and normal cells is different, in part mediated through different levels of activating enzymes like aminopeptidases.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that J1 is a prodrug of melphalan relying on hydrolytic activation by aminopeptidases [10]. In 1999 Martínez et al [13] studied the aminopeptidase activity in surgical specimens from nine breast cancer specimens, and found significantly increased activity of some studied aminopeptidases (for example soluble alanyl, arginyl and cystinyl aminopeptidases) in comparison to normal tissue controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melphalan-flufenamide may thus be considered as a prodrug of melphalan, and its enzymatic activation ( Figure 5.7) is performed by aminopeptidases such as aminopeptidase N (APN). 18 Interestingly, this enzyme is overexpressed in certain malignancies, which provides an opportunity to achieve some tumor selectivity. 19 Estramustine (Estracyt ® , Emcyt ® ), which consists of a β-estradiol unit linked to a nitrogen mustard portion via a carbamate bridge, was designed as a prodrug because the electron-withdrawing effect of the carbonyl group makes the electron density of its nitrogen atom insufficient to trigger aziridinium formation.…”
Section: Site-directed Nitrogen Mustardsmentioning
confidence: 99%